Isolasi Bakteri Indigen Sebagai Pendegradasi Bahan Organik Pada Media Pembenihan Ikan Lele Dumbo (Clarias sp.) Sistem Resirkulasi Tertutup [Isolation Indigen Bacteria In Organic Materials As Media Degrading Seedling Fish Catfish (Clarias sp.) Closed Recirculation System] - Muhammad Arief; Laksmi Sulmartiwi; Prayogo Prayogo; Herlina Maya Saputri (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
Abstract Rearing of African catfish fry requires an abundant water supply, so this causes Clarias gariepinus hatchery operations difficult in areas that lack water, so use a closed recirculation system technology which is an attempt to tackle the problem of limited water in an area for hatchery operations. However, these systems have drawbacks which deposition of organic materials on water quality pond maintenance reduced the need for water quality management. Components of organic materials is a source of water quality pollutants consisting of proteins, lekam, and carbohydrates, so that in the organic material needed pendegradasian existence of groups of bacteria and proteolytic bacteria, lipolytic, and amylolitic. The results of this study show that in the media of African catfish hatchery fish have bacteria that degrade organic material that has properties of proteolytic, lipolytic, and most potentially amylolitic consisting of bacterial isolates of Pseudomonas stutzeri B ie (97.81%) with values highest protease hydrolysis test results 1.878 mm, ie G isolates of Pseudomonas pseudomallei (97.81%) with the highest value of 1.909 mm hydrolysis test and bacterial isolates of Pseudomonas stutzeri K (61.21%) with the highest value of 1.944 mm hydrolysis test.